BUDIDAYA IKAN NILA JATIMBULAN (Oreochromis sp) DENGAN SISTEM SEMI INTENSIF - Rizky, Putri Nurhanida; Aisy, Wulandari Rihhadatul; Primasari, Kartika (Chanos Chanos, 2022)
Low growth performance and survival rate of tilapia is the main problem in tilapia culture especially Nile Jatimbulan. Growth performance of Nile tilapia is highly affected by genetic materials, food quality, stocking density, feeding rate and frequency and environmental factors such as water quality. Semi intensive system in earthen pond were used in this study. Earth pond contain various of organisms which support the growth performance of fish and phytoplankton. In addition, waterwheel with a power of 0.5 HP were added to increase the amount of dissolved oxygen in the pond. To improve water quality and performance of tilapia, EM4 probiotic were applied. This study showed the growth rate of jatimbulan is 2.94 grams, SR 80% and FCR value of 0,6. Jatimbulan tilapia were obtained after 90 days of culture is 6 tons with an average of body weight 250-300 grams.